THE INFLUENCE OF AUDITOR ROTATION AND AUDITOR'S REPUTATION ON AUDIT QUALITY WITH AUDITOR SPECIALIZATION AS A MODERATING VARIABLE - yunita christy; Se Tin Se Tin (Universitas Pendidikan Indonesia, 2021)
This study was conducted to examine how auditor rotation and auditor reputation influence audit quality moderated by audit specialization. The population of this study is using a Consumer Goods Inventory manufacturing company listed on the Indonesia Stock Exchange (IDX) from 2014-2019. This study was using logistics regression analysis to see the influence of auditor rotation, auditor reputation on audit quality, with auditor specialization as a moderating variable. The results showed that auditor rotation had no influence on audit quality; auditor reputation had an influence on audit quality; and auditor specialization could not strengthen the relationship between auditor rotation and audit quality, but could strengthen the relationship between auditor reputation and audit quality.